Draft genome of neurotropic nematode parasite Angiostrongylus cantonensis, causative agent of human eosinophilic meningitis - Yong, Hoi Sen; Eamsobhana, Praphathip; Lim, Phaik Eem; Razali, Rozaimi; Aziz, Farhanah Abdul; Rosli, Nurul Shielawati Mohamed; Poole-Johnson, Johan; Anwar, Arif (Elsevier, 2015)
Angiostrongylus cantonensis is a bursate nematode parasite that causes eosinophilic meningitis (or meningoencephalitis) in humans in many parts of the world. The genomic data from A. cantonensis will form a useful resource for comparative genomic and chemogenomic studies to aid the development of diagnostics and therapeutics. We have sequenced, assembled and annotated the genome of A. cantonensis. The genome size is estimated to be ~260. Mb, with 17,280 genomic scaffolds, 91X coverage, 81.45% for complete and 93.95% for partial score based on CEGMA analysis of genome completeness. The number of predicted genes of ≥300. bp was 17,482. A total of 7737 predicted protein-coding genes of ≥50 amino acids were identified in the assembled genome. Among the proteins of known function, kinases are the most abundant followed by transferases. The draft genome contains 34 excretory-secretory proteins (ES), a minimum of 44 Nematode Astacin (NAS) metalloproteases, 12 Homeobox (HOX) genes, and 30 neurotransmitters. The assembled genome size (260. Mb) is larger than those of Pristionchus pacificus, Caenorhabditis elegans, Necator americanus, Caenorhabditis briggsae, Trichinella spiralis, Brugia malayi and Loa loa, but smaller than Haemonchus contortus and Ascaris suum. The repeat content (25%) is similar to H. contortus. The GC content (41.17%) is lower compared to P. pacificus (42.7%) and H. contortus (43.1%) but higher compared to C. briggsae (37.69%), A. suum (37.9%) and N. americanus (40.2%) while the scaffold N50 is 42,191. This draft genome will facilitate the understanding of many unresolved issues on the parasite and the disorder it causes.